Emotional intelligence as a protective factor of burnout and its consequences in Ecuadorian health personnel (European Journal of Health Research, 2023)
Introduction: Several studies have found that emotional intelligence plays a beneficial role in stress, burnout and mental illness. Studies in the Latin American context and in the health field are scarce. Objectives: to determine the association between emotional intelligence and burnout syndrome in health personnel, as well as the predictive power of emotional intelligence and other physical and psychological health factors in burnout. Methodology: This is a cross-sectional study carried out with 202 professionals from a hospital in Ecuador. The instruments consisted of a survey with sociodemographic and clinical data such as anthropometric measurements and vital signs. The Maslach Burnout Inventory (MBI), the Trait Meta-Mood Scale (TMMS-24) and the PHQ-9 depression screening questionnaire were also used. Results: 71.2% of the participants presented clinical scores on at least one subscale of the MBI. 10.6% showed high emotional exhaustion, 23.7% showed high depersonalization and 50.5% showed low personal accomplishment. 12.4% showed burnout and 11.4% showed moderate to severe levels of depression. Emotional intelligence was found to be negatively associated with burnout and depression. Regression analysis indicates that high scores in depression are explained by the combined effect of excessive emotional attention, high burnout and low emotional repair. Conclusion: Healthcare personnel are exposed to human suffering and death, as well as to high levels of responsibility, which increase in times of crisis. All this leads to burnout, which in turn can lead to depression. It is necessary to implement individual and organizational protection strategies that enhance emotional intelligence as a way to avoid these psychosocial risks.
Keywords: emotional intelligence; healthcare workers; burnout syndrome; depression